IMPLEMENTATION OF THE INDEPENDENT CURRICULUM BY DIGITIZING LEARNING IN ISLAMIC RELIGIOUS COURSES AT PUBLIC UNIVERSITIES - Choli, Ifham; Saputra, Eddy; Rahmawan, Fery; Mujib, Ahmad; Suyana, Nana (Edukasi Islami: Jurnal Pendidikan Islam, 2024)
Religious learning in public universities requires an innovative approach to facing the digital era and implementing the Independent Curriculum. The main focus is technology to increase interaction between students and religious learning materials. Various digitalisation strategies, including online learning platforms, multimedia content, and interactive applications, are described to strengthen understanding of religious concepts and relevant values. The digitalisation of learning in Islamic religious courses on campus will correct deficiencies in conventional learning that have been carried out so far and can answer the challenges and opportunities associated with the digitalisation of religious learning, as well as the implications for student learning experiences and the effectiveness of lecturers' teaching. Through this approach, religious learning in public universities is hoped to become more dynamic, inclusive, and responsive to student needs in the current digital era. The approach to this research uses qualitative methods to understand, explain, and describe phenomena or problems from a more in-depth perspective. This research aims to provide new experiences in learning Islamic religion in public universities and change learning from conventional to digital, which impacts enjoyable learning and achieving learning outcomes.